Prevalence and risk factors for depressive and anxiety symptoms in middle-aged Chinese women: a community-based cross-sectional study - Xueyin Wang; Gengli Zhao; Jiangli Di; Linhong Wang; Xiaosong Zhang (BMC, 2022)
Abstract Background Depression and anxiety have become main public health concerns globally. However, risk factors for depression and anxiety remain unclear. This study was to examine the prevalence and risk factors of depressive and anxiety symptoms in middle-aged Chinese women. Methods This cross-sectional study, conducted in 2018, included 7,727 women aged 40-60 years from the eastern, central and western regions of China. Depressive and anxiety symptoms were determined by the Patient Health Questionnaire-9 and the Generalized Anxiety Disorders-7, respectively. Logistic regression models were used to estimate odds ratios (ORs) for depressive and anxiety symptoms in relation to sociodemographic, lifestyle and menopausal factors. Results Among all participants, 19.5% (1 422/7 275) and 14.2% (1 035/7 275) of participants experienced depressive and anxiety symptoms, respectively. The multivariable logistic regression models showed that age, household income, regular physical activity, chronic diseases, menopausal status, vasomotor symptoms, somatic symptoms and urogenital symptoms were associated with depressive symptoms, while place of residence, regular physical activity, chronic diseases, vasomotor, somatic and urogenital symptoms were associated with anxiety symptoms. Conclusion Depressive and anxiety symptoms were common among middle-aged Chinese women, and certain sociodemographic, lifestyle and menopausal symptoms have an important impact on the risk of depressive and anxiety symptoms.